Islamophobia as Cultural Racism: The Case of Islamic Attire in Turkey - YEL, ALİ MURAT (SETA FOUNDATION, 2021)
Grasping the various aspects of Islamophobia in Muslim societies requires much finer methods in order to decipher the intentions of the actors in distinctive life situations varying from the media to education. This article engages in a debate as to whether Islamophobia is a new type of racism, i.e., cultural, geographical, phenotypical, or Xeno-racism, and the relatively recent type that has emerged in neo-liberal states: anti-Muslim racism. In a Muslim-majority society, the 'culture' of members is fairly homogenous, so Islamophobia takes another cue, focusing on external markers, like the headscarf or beard. While anti-Muslim racism is sometimes exercised along more subtle lines of cultural difference in Muslim societies, it prevails through old-fashioned, phenotypical racism. The representation or rather misrepresentation of Islam and/or Muslims in the media can be understood as the prevailing source of antagonism between the secular and the traditionalist segments of Turkish society; indeed, Turkish media representation produces and reproduces a racialization of the majority, predominately by rendering Islam invisible, or by depicting Muslims in ways that denigrate their clothing manners, style, and way of living across various mass media forms.
Keywords: Islamophobia; Racism; Turkey; Media Representations; Militant Laicism